Alternatives to Paying Child Benefit to the Rich: Means Testing or Higher Tax? - Patricia Apps; Ray Rees; Thor Olav Thoresen; Trine Engh Vattø (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Transferring public benefits to people in no need of them appears to be a waste of public money. Thus, there seems to be support for a move away from universal child benefits and towards means testing. This study presents a critique of this overly-simplistic view and proposes a very simple alternative: instead of withdrawing the transfer as a function of income, which raises marginal tax rates for low and middle income parents, with accompanying detrimental effects on labour supply, redistribution can be achieved by an ambitious universal schedule financed by increased income taxation of the rich. The role of the child benefit is discussed analytically in a piecewise linear schedule. Moreover, the argument is illustrated with reference to the design of the child benefit scheme for Norway, demonstrating the labour supply/redistribution trade-offs of the alternatives by results from simulation models.
Keywords: J13; J22; C25; 330; child benefit; labour supply; income distribution